Evaluating The Effectiveness Of Training Programs In Telekom Training College - Doraisamy, Logama (2000)
The objective of this paper is to measure the effectiveness of the training programs conducted by the five schools of Telekom Training College, the training arm of Telekom Malaysia. The five schools are namely School of Business & Management, School of Human Resource Performance, School of Information Technology, School of Technology and School of Multimedia. The purpose of this study is to identify whether there is any significant difference in the evaluation of the training of the traning programs based on the reactions of the trainees. The model adopted for this study is the Kirkpatrck's 4 level evaluation which has being widely used by the training organizations globally.